Evaluating Cognitive Level Appropriateness of English Textbook Assessment Tasks for First Grade Learners in a Bilingual Elementary School - Maya Febrina; Dedy Subandowo; Fitri Palupi Kusumawati (English Education Study Program, 2026)
This review synthesises existing research on the cognitive levels represented in English textbook tasks, with particular attention to how these demands align with the developmental characteristics of first-grade learners in bilingual elementary settings. Drawing on studies conducted at senior high school, junior high school, and elementary school levels, the review applies Bloom's Revised Taxonomy alongside Piagetian and sociocultural perspectives on child development to examine how lower-order and higher-order thinking skills are distributed across instructional materials. The synthesis reveals a persistent dominance of lower-order cognitive processes across educational levels, with higher-order thinking skills present but inconsistently integrated, and shows that developmental appropriateness is rarely combined with cognitive-level classification as an evaluative criterion. The review further identifies methodological limitations in prior research, including an overreliance on single-framework content analysis and limited attention to task format, scaffolding, and the reliability of coding procedures. Based on these findings, the review argues that evaluating assessment tasks in bilingual first-grade English textbooks requires an integrative framework that combines cognitive classification with developmental and linguistic considerations. It concludes by outlining directions for future research, including classroom-based investigation of how cognitive demands are enacted in practice and closer attention to task design for emergent bilingual readers.